Overexpression of human copper,zinc-superoxide dismutase (SOD1) prevents postischemic injury - Wang, Penghai (The National Academy of Sciences, 1998)
Superoxide and superoxide-derived oxidants have been hypothesized to be important mediators of postischemic injury. Whereas copper,zinc-superoxide dismutase, SOD1, efficiently dismutates superoxide, there has been controversy regarding whether increasing intracellular SOD1 expression would protect against or potentiate cellular injury. To determine whether increased SOD1 protects the heart from ischemia and reperfusion, studies were performed in a newly developed transgenic mouse model in which direct measurement of superoxide, contractile function, bioenergetics, and cell death could be performed. Transgenic mice with overexpression of human SOD1 were studied along with matched nontransgenic controls. Immunoblotting and immunohistology demonstrated that total SOD1 expression was increased 10-fold in hearts from transgenic mice compared with nontransgenic controls, with increased expression in both myocytes and endothelial cells. In nontransgenic hearts following 30 min of global ischemia a reperfusion-associated burst of superoxide generation was demonstrated by electron paramagnetic resonance spin trapping. However, in the transgenic hearts with overexpression of SOD1 the burst of superoxide generation was almost totally quenched, and this was accompanied by a 2-fold increase in the recovery of contractile function, a 2.2-fold decrease in infarct size, and a greatly improved recovery of high energy phosphates compared with that in nontransgenic controls. These results demonstrate that superoxide is an important mediator of postischemic injury and that increasing intracellular SOD1 dramatically protects the heart from this injury. Thus, increasing intracellular SOD1 expression may be a highly effective approach to decrease the cellular injury that occurs following reperfusion of ischemic tissues.